Narrative review of mental illness in cricket with recommendations for mental health support. Issue 1 (29th January 2021) - McCabe, Thomas; Peirce, Nicholas; Gorczynski, Paul; Heron, Neil
Abstract : Introduction: Epidemiology reporting within the cricketing medical literature has emerged over the past 2 years, with a focus on physical injuries. Despite mental health in elite sport gaining increasing recognition, few studies have addressed mental health symptoms and disorders within cricket. Recently, cricketers have been prominent in the mainstream media describing their lived experiences of mental illness. As a result, some have withdrawn from competition and suggested there is an unmet need for mental health services within the sport. Objectives: (i) To appraise the existing evidence on mental health symptoms and disorders amongst cricketers. (ii) To provide guidance on shaping mental health research and services within cricket. Design: A narrative review of the literature from inception of available databases until 26 July 2019, with analysis and recommendations. Results: Five studies were included in this narrative review. Studies covered a range of mental health symptoms and disorders, including distress, anxiety, depression, sleep disturbance, suicide, adverse alcohol use, illicit drug use, eating disorders and bipolar disorder. Results indicated that cricketers are at high risk for distress, anxiety, depression and adverse alcohol use. When compared with the general population, cricketers are more likely to experience anxiety and depressive symptoms. Rates of suicide were proposed to be high for test cricketers. Overall, studies to date have been of low quality, demonstrating non-rigorous research methods. Some studies have relied on non-validated questionnaires to collect self-reported data on mental health symptoms and disorders, while others have presented biographical data obtained through searches of the media. Conclusions: The results of this narrative review highlight the lack of evidence underpinning mental health services for athletes within cricket. We suggest the following recommendations for future research and practice: (i) normalising mental health symptoms and disorders; (ii) working with and helping vulnerable demographic segments within the target population; (iii) designing and implementing early recognition systems of mental health symptoms and disorders; (iv) addressing the mental health needs of cricketers on a population basis.